Holographic Dark Energy in the Dgp Model - Cruz-Marin, N (Springer New York LLC, 2012)
The braneworld model proposed by Dvali, Gabadadze, and Porrati leads to an accelerated universe without cosmological constant or any other form of dark energy. Nevertheless, we have investigated the consequences of this model when an holographic dark energy is included, taking the Hubble scale as IR cutoff. We have found that the holographic dark energy leads to an accelerated flat universe (de Sitter-like expansion) for the two branches: ?{lunate}=±1, of the DGP model. Nevertheless, in universes with no null curvature the dark energy presents an EoS corresponding to a phantom fluid during the present era and evolving to a de Sitter-like phase for future cosmic time. In the special case in which the holographic parameter c is equal to one we have found a sudden singularity in closed universes. In this case the expansion is decelerating. © 2012 Springer-Verlag Berlin Heidelberg and Società Italiana di Fisica.